2000
DOI: 10.1021/jp993723h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conduction Properties of PVDF−HFP Type Gel Polymer Electrolytes with Lithium Imide Salts

Abstract: Conduction properties of gel polymer electrolytes composed of lithium imide salts, LiN(CF3SO2)2, LiN(C2F5SO2)2, and PVDF−HFP copolymer were investigated using the pulsed-field gradient NMR and complex impedance techniques. The diffusion coefficients of the gel decreased with an increase in the polymer fraction in the gel. Carrier concentration exhibited 3 orders of magnitude variation in the fraction change in polymer from 80% to 20%. These results suggest that the polymer interacts with the electrolyte to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 10 publications
4
96
0
Order By: Relevance
“…The relation between viscosity and mobility as given in the introduction part generally hold good for liquid electrolytes as well as for gel electrolytes at low concentrations of polymer but may not hold good at higher concentrations of polymer, where the difference between microand macro-viscosity becomes large. Similar results has also been observed for some proton conducting polymer gel electrolytes containing different weak carboxylic acids [14,[18][19][20] as well as for some lithium ion conducting polymer gel electrolytes [21][22][23]. The increase in conductivity with polymer addition is generally ascribed to be due to an increase in free ion concentration, although the exact mechanism is not yet clearly understood.…”
Section: Gel Electrolytessupporting
confidence: 79%
“…The relation between viscosity and mobility as given in the introduction part generally hold good for liquid electrolytes as well as for gel electrolytes at low concentrations of polymer but may not hold good at higher concentrations of polymer, where the difference between microand macro-viscosity becomes large. Similar results has also been observed for some proton conducting polymer gel electrolytes containing different weak carboxylic acids [14,[18][19][20] as well as for some lithium ion conducting polymer gel electrolytes [21][22][23]. The increase in conductivity with polymer addition is generally ascribed to be due to an increase in free ion concentration, although the exact mechanism is not yet clearly understood.…”
Section: Gel Electrolytessupporting
confidence: 79%
“…We found that the interaction between the salt (and/or ion) and the polymer in the gel dominates the mobility and concentration of the carrier in the PVDF type gel. [2][3][4][5][6] Control of the interactive effect is indispensable for designing gel electrolyte material, which provides high conductivity and safety performance.…”
Section: Introductionmentioning
confidence: 99%
“…19,31 Table 1 shows the diffusion coefficients for both ions and the solvent molecules in the pure liquid electrolyte and in the gel polymer electrolyte. For the determination of each diffusion coefficient, two samples were prepared and measured at diffusion times Δ 40 ms and at Δ 100 ms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%